CRISPR/Cas9 Deletion of SOX2 Regulatory Region 2 (SRR2) Decreases SOX2 Malignant Activity in Glioblastoma - Saenz-Antoñanzas, Ander (Cancers (Basel), 2021)
SIMPLE SUMMARY: Understanding how SOX2, a major driver of cancer stem cells, is regulated in cancer cells is relevant to tackle tumorigenesis. In this study, we deleted the SRR2 regulatory region in glioblastoma cells. Our data confirm that the SRR2 enhancer regulates SOX2 expression in cancer and reveal that SRR2 deletion halts malignant activity of SOX2. ABSTRACT: SOX2 is a transcription factor associated with stem cell activity in several tissues. In cancer, SOX2 expression is increased in samples from several malignancies, including glioblastoma, and high SOX2 levels are associated with the population of tumor-initiating cells and with poor patient outcome. Therefore, understanding how SOX2 is regulated in cancer cells is relevant to tackle tumorigenesis. The SOX2 regulatory region 2 (SRR2) is located downstream of the SOX2 coding region and mediates SOX2 expression in embryonic and adult stem cells. In this study, we deleted SRR2 using CRISPR/Cas9 in glioblastoma cells. Importantly, SRR2-deleted glioblastoma cells presented reduced SOX2 expression and decreased proliferative activity and self-renewal capacity in vitro. In line with these results, SRR2-deleted glioblastoma cells displayed decreased tumor initiation and growth in vivo. These effects correlated with an elevation of p21(CIP1) cell cycle and p27(KIP1) quiescence regulators. In conclusion, our data reveal that SRR2 deletion halts malignant activity of SOX2 and confirms that the SRR2 enhancer regulates SOX2 expression in cancer.